Morphology and Phase Composition of Particles Produced by Electro-Discharge-Machining of Iron - Cabanillas, E. D. (2001)
Towards producing metallic particles of controlled size and spherical shape, which are of technological importance, we have collected in the filters of an electro-discharge-machine (EDM) the material ejected from the surface of EDM iron pieces. The conditions of machining were varied for kerosene and water as dielectrics, using a discharge current of 25 A and duration times of 16 and 3072 μs for kerosene and of 32, 384 and 768 μs for water, respectively. Scanning electron microscopy was used to assess the effect of the time of discharge on the size of the particles. Mossbauer spectroscopy and X-ray diffraction revealed that for kerosene EDM particles only cementite-like carbides of diverse stoichiometry were formed. While no oxide was found for kerosene spheres, the analyses showed that besides the main fraction of α-Fe, a small percentage of wustite (and traces of hematite for the 384 μs sample) formed on the water EDM ones.